Transcriptome analysis of the inflammatory responses of bovine mammary epithelial cells: Exploring immunomodulatory target genes for bovine mastitis - Islam, Md Aminul (2020)
Bovine mastitis is the inflammatory reaction of the mammary gland and is commonly caused by bacterial infections in high-yielding dairy cows. The detailed investigation of the immunotranscriptomic response of bovine mammary epithelial (BME) cells to pattern recognition receptors (PRRs) activation by microbial-associated molecular patterns (MAMPs) can be of great importance for understanding the innate immune defense mechanisms, and for exploring the immunomodulatory candidate genes. In this work, we investigated the transcriptome modifications of BME cells after the in vitro stimulation with Escherichia coli derived lipopolysaccharide (LPS) and heat-killed Staphylococcus aureus JE2 and S. aureus SA003. In addition, the effect of Pam3CSK4 (a synthetic triacylated lipopeptide that activates Toll-like receptor 2 (TLR2)), and the intracellular chemotactic protein cyclophilin A (CyPA), which is secreted by BME cells during mastitis, in the expression changes of selected cytokines and chemokines were evaluated by qPCR. Microarray analysis identified 447, 465 and 520 differentially expressed genes (DEGs) in the BME cells after LPS, S. aureus JE2 and S. aureus SA003 stimulation, respectively. A major differential response in the inflammatory gene expression was noticed between the stimulation of LPS and S. aureus strains. Unlike the S. aureus strains, LPS stimulation resulted in significant upregulation of CCL2, CXCL2, CXCL3, CXCL8, IL1α and IL1β, which were confirmed by qPCR analysis. Pam3CSK4 was not able to induce significant changes in the expression of cytokines and chemokines in challenged BME cells. The exogenous CyPA administration was able to upregulate CXCL2, CXCL3, CXCL8, IL1α and IL1β expression in BME cells indicating its ability to promote inflammation. The identification of transcriptional markers of mastitis specific for individual inflammatory factors such as LPS, Pam3CSK4 or CyPA, which can be evaluated in vitro in BME cells, may enable the development of novel diagnostics and/or immunomodulatory treatments, providing new tools for the effective management of mastitis in dairy cows. The results of this work are an advance in this regard.